Extracorporeal photopheresis for the treatment of chronic graft versus host disease. Issue 1 (31st December 2022) - Kansu, Emin; Ward, David; Sanchez, Amber P.; Cunard, Robyn; Hayran, Mutlu; Huseyin, Beril; Vaughan, Majella; Ku, Grace; Curtin, Peter; Mulroney, Carolyn; Costello, Caitlin; Castro, Januario E.; et al.
ABSTRACT: Objectives: Chronic graft versus host disease (chronic GVHD) still remains the leading cause of late morbidity and mortality for allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients. In this retrospective study, 53 consecutive allo-HSCT patients with chronic GVHD refractory to corticosteroids were treated with extracorporeal photopheresis (ECP). Methods: This study was performed as a retrospective single-center study. Medical records of a total of 59 patients treated with ECP for chronic GVHD were reviewed. Results: Best organ responses to ECP were observed in skin, mouth mucosa, eyes and liver. Overall response rate (ORR) to ECP was 81.2% (CR 17% and PR 64.2%). Overall survival (OS) was 84.9% and 36.7%, at 1 and 3 years, respectively. Female sex appears to have an advantage on ORR. Patients achieving ORR were able to maintain their responses with a prolonged continuation of treatments for +6 and +12 months indicating the benefits of longer ECP treatment. Discussion: We found that patients with chronic GVHD who were treated with ECP for 12 months or longer had a higher response rate. Our findings in line with the data reported previously suggest that patients responding to ECP should continue longer therapy schedules to achieve a better and sustained response. In our cohort, long-term ECP therapy was safe and well-tolerated with no significant adverse effects. Best responses were observed in the patients with skin, eye, liver and oral involvement. The ECP procedure offers the advantage relative to the problems with typical immunosuppressive agents. The female sex appeared to have an advantage based on the cumulative probability of the OR after ECP for chronic GVHD.